Developing and Validating a Positive Psychology Model of Flourishing in EFL Contexts: A Structural Equation Modeling Study - Davaribina, Mehran; Pazhouhesh, Seyed Rahman (Assessment and Practice in Educational Sciences, 2027)
Background: Over the past decade, Positive Psychology has gained substantial momentum in Second Language Acquisition (SLA). However, flourishing as a multidimensional higher-order construct has remained underexplored in English as a Foreign Language (EFL) context. Objective: This study developed and validated a structural model of flourishing in EFL settings, grounded in Positive Psychology and Self-Determination Theory. Methods: A quantitative cross-sectional design was employed. Data were collected from 450 EFL learners in Iran. Confirmatory Factor Analysis (CFA) and second-order Structural Equation Modeling (SEM) were used to test the measurement and structural models. To address potential methodological concerns, supplementary analyses including partial correlations, independent samples t-tests, one-way ANOVA, MANOVA, and non-parametric tests (Mann-Whitney U and Kruskal-Wallis) were also conducted to examine the robustness of the findings and the influence of demographic variables. Results: The measurement model demonstrated excellent fit (CFI = 0.94, TLI = 0.92, RMSEA = 0.06, SRMR = 0.05). Flourishing was validated as a second-order latent construct comprising positive emotion, engagement, relationships, meaning, and accomplishment. Foreign Language Enjoyment (β = 0.42), teacher support (β = 0.35), self-determined motivation (β = 0.38), and academic resilience (β = 0.31) significantly predicted flourishing. Flourishing significantly predicted academic engagement (β = 0.52) and language achievement (β = 0.29). Supplementary analyses confirmed the stability of these relationships. Specifically, a significant partial correlation was found between Foreign Language Enjoyment and academic resilience (r = 0.39, p < .01) after controlling for age. Furthermore, no significant differences in flourishing were observed based on gender (t(448) = 1.45, p = .14) or age group, as confirmed by ANOVA (F(2, 447) = 0.98, p = .37) and Kruskal-Wallis tests (H(2) = 4.21, p = .12), reinforcing the generalizability of the model across these demographic factors. Conclusion: This study introduces flourishing as an integrative well-being construct in SLA, validates a second-order SEM model, and provides a comprehensive framework for understanding optimal psychological functioning in EFL learning environments.